Improving Maritime Education for Sustainability and Industry Alignment - A Qualitative and Systematic Literature Review - Barasa, Larsen; Winarno; Kuntadi, Cris; Permana, Aji; Simanjuntak, Marudut Bernadtua (Lembaga Einstein College (LEC), 2025)
This study explores the integration of sustainability into maritime education and its alignment with the evolving demands of the maritime industry. The research was motivated by the increasing necessity for maritime professionals to possess both technical expertise and a strong understanding of sustainable practices in response to environmental concerns. Previous studies have emphasized sustainability as a theoretical concept, yet practical insights from maritime professionals, educators, and graduates have been underexplored. The study addresses three key questions: How is sustainability incorporated into maritime curricula? How well do vocational programs match industry needs? How do the perspectives of professionals, educators, and graduates contribute to refining maritime education? A qualitative research approach was used, consisting of interviews with two maritime experts, six educators, and two graduates, complemented by a systematic literature review (SLR) to analyze current trends and gaps. Findings reveal significant progress in sustainability integration, although practical implementation and continuous professional development require further attention. The SLR supported these conclusions, stressing the importance of interdisciplinary curricula. The research concludes that aligning education with industry needs and embedding sustainable practices into programs are crucial for preparing a skilled maritime workforce. Practical recommendations are offered for both educational institutions and the maritime sector, with suggestions for future research on green technologies and ongoing professional development.